2011
DOI: 10.1128/ec.05185-11
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Polymerase II Transcription Initiation in Trypanosoma cruzi: Modulation of Nucleosome Abundance, Histone Modification, and Polymerase Occupancy by O-Linked Thymine DNA Glucosylation

Abstract: Very little is understood regarding how transcription is initiated/regulated in the early-diverging eukaryote Trypanosoma cruzi. Unusually for a eukaryote, genes transcribed by RNA polymerase (Pol) II in T. cruzi are arranged in polycistronic transcription units (PTUs). On the basis of this gene organization, it was previously thought that trypanosomes rely solely on posttranscriptional processes to regulate gene expression. We recently localized a novel glucosylated thymine DNA base, called base J, to potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…Interestingly, 5-formylcytosine and 5-carboxycytosine can significantly reduce the kinetics of yeast RNA polymerase II transcription, suggesting that these modifications play a role in splicing and termination (46) intriguing because the studies demonstrating the role of base J in Pol II transcription were performed by halting hmU synthesis via altering JBP function (5)(6)(7). Future experiments utilizing the JGT KO cell line will allow us to address the specific role of hmU, fU, and base J in regulating Pol II kinetics and trypanosomatid gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 5-formylcytosine and 5-carboxycytosine can significantly reduce the kinetics of yeast RNA polymerase II transcription, suggesting that these modifications play a role in splicing and termination (46) intriguing because the studies demonstrating the role of base J in Pol II transcription were performed by halting hmU synthesis via altering JBP function (5)(6)(7). Future experiments utilizing the JGT KO cell line will allow us to address the specific role of hmU, fU, and base J in regulating Pol II kinetics and trypanosomatid gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of base J at transcription start sites coincides with a decrease in nucleosome abundance, increased histone acetylation, and increased Pol II occupancy at promoter regions (3,4). This increase in Pol II recruitment correlates with an increased rate of transcription initiation and changes in gene expression (3). These studies indicate the importance of epigenetic regulation of Pol II transcription via DNA modification and chromatin structure in kinetoplastids as well as provide a mechanism for J regulation of trypanosome gene expression.…”
mentioning
confidence: 67%
“…We have previously demonstrated that reduced J levels in T. cruzi results in increased Pol II recruitment to promoter regions and an increase in the rate of transcription initiation, which in turn causes global changes in gene expression (3,4). Notably, surface proteins involved in parasite pathogenesis (including members of the trans-sialidase and mucin gene family) are significantly affected during reduced J levels.…”
Section: Jbp Activity Is Regulated By Oxygen Levels In Vivo-given Thamentioning
confidence: 99%
See 2 more Smart Citations